Highlighting the Link between Parkinson’s Disease and Malignant Melanoma: A Case Report and Literature Review - Natassja Moriarty (European Journal of Case Reports in Internal Medicine, 2019)
The aim of this case report and literature review is to explore the rarely highlighted co-occurrence of malignant melanoma and Parkinson’s disease (PD) and to describe the devastating effects on those affected. We present a case of acute confusion and worsening shuffling gait in a patient with Parkinson’s disease who eventually succumbed to metastatic malignant melanoma, secondary to a primary malignant melanoma on the back that was treated 6 years earlier. More research is needed to better characterize the associations between these two conditions, and to evaluate the effectiveness of prevention strategies such as melanoma screening for adults with PD.